A re-definition of belonging? : language and integration tests in Europe - Oers, Ricky van; Ersbøll, Eva; Kostakopoulou, Theodora (Immigration and asylum law and policy in Europe, 2010)
Language and integration tests as a condition for naturalisation and various types of legal residence permits are topical issues in several European Member States. The introduction of the tests reflects a change in ideas on the relationship between legal status and integration. Since the introduction of the tests is a rather recent development, little is known of the effects of the formalised testing schemes. Whether the tests have in fact contributed to the integration of immigrants in the host society or whether they function as a mechanism for selection and exclusion is unknown. In this boo.